Occupational Therapy Education and Entry-Level Practice: A Systematic Review - Srdjan Lemez; Dominic Jimenez (MDPI AG, 2022)
Occupational therapists can currently enter clinical practice with either a master's or clinical doctorate-level degree, as mandated by the American Occupational Therapy Association (AOTA); however, the single vs. dual points of entry remains a topic of debate among practitioners and stakeholders. This systematic review addresses the question of whether existing knowledge around this topic provides defensible policy decision making. As such, the overarching objective was to expound on this current issue in education by aggregating existing literature and synthesizing data related to entry mandates to practice occupational therapy (OT). From 20 May to 20 June 2021, a systematic search of three electronic scientific databases (Web of Science, PubMed, and Sports Medicine and Education Index) and the Google Scholar database was performed. Following the 2020 PRSIMA guidelines, a total of 15 articles met our established inclusion criteria, which included: (1) publication date from 1 January 2008 or later; (2) North American OT programs only; (3) articles that specifically focused on OT and entry-level degree requirements; and (4) articles published in English. Bias was assessed using risk level categorizations recommended by Cochran Collaboration. Participants across the articles included in this review (N = 1749) ranged from OT practitioners and assistants, program directors, and supervisors, to current students, graduates, and faculty. Results were categorized into two central themes related to each side of the debate, and findings indicated that a majority of the participants support maintaining two entry points into the profession, despite compelling arguments having been made for both sides. The authors acknowledge the presence of several limitations in the included studies and advocate that more evidence-based research focusing on objective measures, rather than commentaries and opinions, of clinical performance outcomes between the two OT degree groups is needed to ensure that patient needs continue to be effectively addressed and policy decision making is justifiable.